Cell-free circulating tumor RNAs in plasma as the potential prognostic biomarkers in colorectal cancer - Jin, Nana; Kan, Chau-Ming; Pei, Xiao Meng; Cheung, Wing Lam; Ng, Simon Siu Man; Wong, Heong Ting; Cheng, Hennie Yuk-Lin; Leung, Wing Wa; Wong, Yee Ni; Tsang, Hin Fung; Chan, Amanda Kit Ching; Wong, Yin Kwan Evelyn; et al. (Frontiers in Oncology, 2023)
Cell free RNA (cfRNA) contains transcript fragments from multiple cell types, making it useful for cancer detection in clinical settings. However, the pathophysiological origins of cfRNAs in plasma from colorectal cancer (CRC) patients remain unclear. To identify the tissue-specific contributions of cfRNAs transcriptomic profile, we used a published single-cell transcriptomics profile to deconvolute cell type abundance among paired plasma samples from CRC patients who underwent tumor-ablative surgery. The transcriptomic component from intestinal secretory cells was significantly decreased in the in-house post-surgical cfRNA. We further validated the differentially expressed cfRNAs in 5 pairs of CRC tumor samples and adjacent tissue samples as well as 3 additional CRC tumor samples using RNA-sequencing. The HPGD, PACS1, and TDP2 expression was consistent across cfRNA and tissue samples. Using the Cancer Genome Atlas (TCGA) CRC datasets, we were able to classify the patients into two groups with significantly different survival outcomes. The three-gene signature holds promise in applying minimal residual disease (MRD) testing, which involves profiling remnants of cancer cells after or during treatment. Biomarkers identified in the present study need to be validated in a larger cohort of samples in order to ascertain their possible use in early diagnosis of CRC.